What can functional linguistics contribute to transforming health discourses and health care? / Alison Rotha Moore - Moore, Alison Rotha (Akademi Pengajian Bahasa, 2021)
In considering the conference theme of ‘engaging in change’, one question that needs asking is: where should we – linguistics, literature and languages – focus our efforts towards social transformation? A related question soon follows: how do we need to change to make the most useful contribution we can make? In other words, our disciplines should ultimately empower others, but we may need to charge them up to achieve that! As a researcher and educator working mostly with systemic functional linguistics and medicine, I argue that healthcare communication is one field where there is much for us to contribute. But, since healthcare – and therefore healthcare communication – is a relatively weak determinant of health itself, perhaps as low as 15% (McGinnis et al. 2002), our focus also needs to broaden to the many other ways that discourse shapes opportunities for human health and flourishing (Moore 2019). As well as describing some projects from our Health Semiotics Lab at University of Wollongong and Centre for Language in Social Life at Macquarie University, e.g., on psychotherapy, cancer care, surgical interaction, and medicines information/advertising, I will sketch some broad linguistic themes that I hope will raise discussion around conceptual tools that can empower us. For example I will argue that, like language, health care can be seen as a complex realizational system (Butt, Moore and Cartmill 2016): for anything to happen at all in either language or healthcare, it must happen on a number of different levels of abstraction, where relations between levels are realizational rather than causal. Other fruitful linguistic concepts that have been underutilized in health research include register (Halliday 2007[1964]; Moore 2020); the related concept of meaning potential and of patients as meaners and the implications of this for patient-centred care (Matthiessen 2013); plus Hasan’s notions of cohesion and cohesive harmony (1985) and her innovative system network approach to analysing relations between language and context (2009). Such tools help model patient-professional and inter-professional communication as complex, joint accomplishments that respond to and create contextual shifts and which are always culturally embedded. The tools can be used across spoken, written, graphic and proxemic modes of communication, but challenges remain in adapting tools across modes and contexts. Other challenges include the need for language specialists to better understand the theoretical and methodological plurality of healthcare and health research, and translating research into pedagogy, policy and practice.